Enhanced protection against Q fever in BALB/c mice elicited by immunization of chloroform-methanol residue of Coxiella burnetii via intratracheal inoculation. Issue 41 (24th September 2019) - Feng, Junxia; Hu, Xueyuan; Fu, Mengjiao; Dai, Lupeng; Yu, Yonghui; Luo, Wenbo; Zhao, Zengming; Lu, Zhiyu; Du, Zongmin; Zhou, Dongsheng; Wen, Bohai; Jiao, Jun; et al.
Abstract: Human Q fever is recognized as a worldwide public health problem. It often occurs by inhalation of airborne aerosols contaminated with Coxiella burnetii, a gram-negative intracellular bacterium, mainly from domestic livestock. In this study, we analyzed the possibility to establish mucosal and systemic immunity against C. burnetii infection using a pulmonary delivery of chloroform-methanol residue of C. burnetii (CMR) vaccine. Mice were immunized by the intratracheal inoculation of CMR (IT-CMR) or the subcutaneous injection of CMR (SC-CMR), and the immunized mice were challenged with C. burnetii by the intratracheal route. The levels of IFN-γ, IL-12p70, IL-5, and IL-4 in the IT-CMR group in splenic T cells stimulated ex vivo were significantly higher than in the SC-CMR group. Significantly elevated sIgA to C. burnetii was detected in the bronchoalveolar lavage fluid of mice immunized by IT-CMR but not by SC-CMR, which might have contributed to the significant reduction in C. burnetii load and pathological lesions in the lungs of the mice after the challenge of C. burnetii . These results suggest that compared with SC-CMR in mice, IT-CMR was more efficient to elicit cellular and lung mucosal immune responses against aerosol infection of C. burnetii .